A selective and low impacting traditional fishery, sustaining the economy of small coastal villages in central Mediterranean: Keep or replace the small‐scale driftnets?. (24th October 2019) - Sartor, Paolo; Carbonara, Pierluigi; Cerasi, Sandro; Lembo, Giuseppe; Facchini, Maria Teresa; Lucchetti, Alessandro; Sabatella, Rosaria Felicita; Musumeci, Claudia; Zupa, Walter; Spedicato, Maria Teresa
Abstract: Small‐scale driftnets (SSDs) have been historically used in the Mediterranean without major environmental concern. The introduction of large‐scale driftnets caused unwanted catches of protected species. Specific regulations were therefore issued in European waters, culminating in a proposed moratorium on SSDs. This study aimed to characterise the SSD fishery targeting anchovy (menaide), evaluating its environmental sustainability, economic performance and social relevance. In 2013, a survey by interviews, logbooks and observers on board assessed the order of magnitude of this fishery in terms of fishing capacity and activity, volume of landings and revenues. The menaide fleet consisted in 60 vessels <12 m overall length, moored in little harbours in southern Italy. These nets are highly selective: the target species, European anchovy, Engraulis encrasicholus (L.) and sardine, Sardina pilchardus (Walbaum), dominates the catches, while discards are negligible. The anchovies caught are of high quality and large size; the high prices support fish processing by local factories. Moreover, the results of a SWOT analysis demonstrated that replacing SSDs with a semi‐industrial fishery, like purse seining, would increase impacts on the ecosystem, and a loss of socio‐economic opportunities for several coastal villages. These findings support the option of keeping SSDs operating, in the framework of specifically oriented management measures.